CONSTRUCTING AND STANDARDIZING A MEASURE OF THINKING STYLES ACCORDING TO THE NEETHLING MODEL FOR VOLLEYBALL COACHES REGISTERED IN THE IRAQI CENTRAL FEDERATION (ResearchJet Journal of Analysis and Inventions, 2022)
e importance of the research lies in identifying the level of thinking with its different methods among volleyball coaches. To achieve the best achievement and high efficiency. It is important for the trainers to recognize the patterns of thinking necessary for them according to the neurons controlling them and guiding their behaviour. To be able to deal with the players in a way that achieves better learning for them. And since the trainers deal with heterogeneous human spectra with individual differences and different psychological tendencies and tendencies; There was a need to prepare a generation of coaches with creative and positive thinking and influencing the hearts of the players. Hence, the research problem arises, that is, the difficulties and problems that volleyball coaches face in order to achieve the goals set for the players, which will reflect positively on their creativity in performing the training units in a way that rises to the level of creativity and achievement. The research aims to identify the methods of thinking and build a scale for it according to the Neathling model for volleyball coaches registered in the Iraqi Central Federation. The descriptive survey method was the method that the researcher followed in his study. Due to its suitability to the nature of the study.